Factors Affecting Guest Satisfaction at The Haven Bali Seminyak Hotel: Faktor-Faktor yang Mempenggaruhi Kepuasan Tamu Pada Hotel The Haven Bali Seminyak - Eligion, Perdamiano; Sukmana, IWK Teja; Mertayasa, I Gede Agus (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2025)
This study identifies and analyses factors influencing guest satisfaction at The Haven Bali Seminyak Hotel. Guest satisfaction is an essential factor in the sustainability of the hotel business, especially amidst the tight competition of the Bali tourism industry. This study uses a quantitative approach with a factor analysis method on 150 respondents selected through the Accidental Sampling technique. Data were collected using a questionnaire with 15 indicators, with the help of SPSS 25 for Windows software. Factor analysis identifies four factors influencing guests' staying at The Haven Bali Seminyak Hotel. These four factors consist of (1) Technical Service Quality, (2) Service Procedures and Efficiency, (3) Human Resources, and (4) Employee Responsiveness. In this study, technical service quality is the dominant factor determining guest satisfaction at The Haven Bali Seminyak Hotel. Based on this study's results, improving technical service standards is recommended. Through increasing accuracy in repairing damaged facilities, accelerating responses to guest requests, and ensuring all work equipment is in good condition and ready to use, regular training for employees directly involved in service needs to be improved so that they can provide services quickly, accurately, and in a friendly manner.